Effect Of Comprehensive Income In Market Value Of Company Importance Of Comprehensive Income In Market Value Of - سلمان, عامر محمد; حسب الله, احمد سامي (Journal of Economics and Administrative Sciences, 2012)
The study aims (objective ) to clarify the concept of comprehensive income and its usefulness for users, as the study aims to clarify the relationship between the concept of comprehensive income and market value of the company where the measurement of comprehensive income after accounting for net income and by measuring the unrealized gains or losses in the value of securities available for sale, and measurement the unrealized gains or losses on futures contracts, which are financial derivatives, and measurement the unrealized gains or losses from the settlement of foreign currency translation (conversions), and measurement the impact on the market value of companies and of the present study to rise or fall of return on the stock.The study focused to clarify the extent to which Iraqi firms, including banks in the application of the concept of comprehensive income on its financial statements. Where the concept of comprehensive income of topics relatively new, and began to offer the proposal of comprehensive income in the financial statements in a special supplement to the income statement or in the statement of other income caused the main menu or a Statement of common include all items of comprehensive income or to offer as part of the statement of equity owner. The research related by comprehensive income relatively few , study focused display and explain the concept of comprehensive income and measuring its impact on the market value of the companies, and the extent to which companies such as Iraqi banks to include a statement of comprehensive income in a statement of separate with reference to a marginal note in the statement of income.Which includes the income statement in accordance with this input from all operations (transactions) and economic events that took place in the company during the accounting period so as to include all the items of the profit or loss resulting from normal operations or (frequency) duplicate of the main activities of this company, in addition to the items of unrealized gains and losses and any other items incidental unusual or non-recurring.